THE EFFECT OF USING FLIPPED LEARNING STRATEGY IN IMPROVING STUDENTS’ SPEAKING SKILL IN HYBRID LEARNING - Verina Ainur Izzami Hariyanto; Yuri Lolita (Universitas Muhammadiyah Tangerang, 2023)
The purpose of the study was to determine the the effect of the Flipped Classroom method application on students' speaking skill in hybrid learning. The term